Digital Workplace Monitoring and Employees’ Privacy Rights in Indonesia - Atmari Atmari; Sudjai Sudjai (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
Digital workplace monitoring has expanded significantly alongside the rapid development of digital technology, raising legal concerns regarding the legitimacy of employer surveillance and the protection of employees’ privacy rights. This study examines the legal basis of employers’ authority to conduct digital monitoring, analyses the extent of legal protection afforded to employees’ privacy rights, and identifies normative gaps within Indonesian labour and personal data protection regulations. This research employs a normative legal method using statutory, conceptual, and comparative approaches. The study finds that digital monitoring constitutes part of employers’ managerial prerogatives; however, its implementation must comply with the principles of legality, necessity, proportionality, transparency, and accountability. The findings further demonstrate that employees’ privacy protection in Indonesia remains inadequate due to regulatory fragmentation and the unequal bargaining position of workers in employment relationships, which often renders consent merely formalistic. In addition, the absence of specific regulations governing workplace digital surveillance creates legal uncertainty and increases the risk of excessive monitoring practices. This study proposes strengthening the integration between labour law and personal data protection law, alongside the establishment of specific legal standards governing workplace digital surveillance in Indonesia. The novelty of this study lies in its formulation of a legal framework that balances employers’ managerial interests with the protection of employees’ privacy rights in the digital workplace.